The Use of Debating Activities to Improve Student's Speaking Skill - Era Astati (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2019)
Speaking skill is one of  important elements in English. The teacher can see the process of students in studying English by seeing their speaking skill.  The purpose of this research is to find out whether debating activities can better improve the students’ speaking skill. This reseach was conducted at the third year students of STIKes YPAK Padang. This research used action research. The researcher collected data from test, observation  and interview. It was found that the students’ speaking skill by using debating activities could better improve than before the research was conducted. The researcher found that the average score of the pre test was 48,1. The everage score in the first cycle was 51,4. So, the result score from pre test to cycle 1 was a little improvement. Then the everage score in the second cycle was 70,3. In the second cycle there was good improvement in speaking. In short, debating activities could improvement the students’ speaking skill at the third year students of  STIKes YPAK Padang.